Pengaruh Pendidikan Karakter terhadap Hasil Belajar Siswa SMA: Literature Review - Rudeva, Ami Dwinanda; Anugrah, Chici; Naitul, Messy; Ardi, Ardi (TSAQOFAH, 2024)
The Indonesian government through the Ministry of Education has implemented this system of character formation through education, starting from elementary to tertiary level. Character education is genuine education, or education that teaches people what character actually is in the three dimensions, namely. The aim of this research is to (find out the influence of the character of education on student learning outcomes. This research was conducted using a correlational descriptive research design. The method used was meta-analysis literature review of five previous research articles to search for records searched through the Google Scholar database using the keyword education character, learning outcomes and high school. The results of the research show that character education influences the learning outcomes of high school students.